Assessing the Impact of a Structured Immunization Education Program on Knowledge and Attitudes Among New and Expecting Mothers in Bengaluru, India: A Quasi-Experimental Design - Jain, Ashish; Bose, Angja Khera (Journal of Social Science and Humanities, 2025)
Introduction: Immunization is vital; it protects nearly 3/4th of children against major Childhood illness. There are several diseases, which can be easily prevented by timely Vaccination as a part of routine immunization. Every child has the right to benefit from the appropriate traditional and new life saving vaccinations. All mothers wish Good health for their children. Health workers desire all children immunized against Vaccine preventable diseases. The government wants them protected from progressive Diseases. But many vaccines do not reach a majority of infants and children. Decreased awareness, patient compliance and cost effectiveness play a major role in Limiting the success of vaccine. Children are innocent, trusting and full of hope.1 Aim of the study: To evaluate the effectiveness of structured teaching program on knowledge And attitude regarding immunization among mothers of under five children in Term of gain in post test knowledge and attitude score. Material and methods: Purposive sampling technique was used. Sample size of this study consists of 30 mothers of under five children living in selected community area at. Marenahalli. The investigator developed a questionnaire and likert scale to assess the attitude of mother with under five children. Results: Regarding Age of the mother, maximum 15 (50%) mothers were between the ages of 24-28. Regarding Religion, maximum 17 (56.66%) mothers were Hindu. Regarding education of the mother, maximum 9(30%) mothers were completed primary education, 8(26.66%) mothers had no formal education. Regarding source of information, maximum 8(26.66%) mothers were got the information through the radio. In pre test, the majority of the mothers 16(53.33%) had inadequate knowledge regarding immunization. In post test, the majority mothers 25(83.33%) had moderate knowledge regarding immunization. In pre test, the majority of the mothers 19(63.33%) had poor attitude regarding immunization. In post test, the majority mothers 24(80%) had average attitude regarding immunization. While comparing the pre test (mean score 11.16) knowledge score regarding immunization most of the mothers were scored more in the post test (mean score 14.2). While comparing the pre test (mean score 14.6) attitude score regarding immunization most of the mothers were scored more in the post test (mean score 17.4).There is significant association between knowledge and age of the mother and occupation of the mother. But there was no association between religion, education and source of information with the post test knowledge score.-There is significant association between attitude and age of the mother and occupation of the mother. But there was no association between religion, education and source of information with the post test attitude score.